Novel and practical asymmetric synthesis of β2, 3-amino esters using asymmetric Michael addition of chiral amine. Issue 15 (13th April 2017) - Ozeki, Minoru; Egawa, Honoka; Takano, Toshiki; Mizutani, Hideki; Yasuda, Narumi; Arimitsu, Kenji; Kajimoto, Tetsuya; Hosoi, Shinzo; Iwasaki, Hiroki; Kojima, Naoto; Node, Manabu; Yamashita, Masayuki
Abstract: A practical method for the synthesis of chiral β 2, 3 -amino esters having various substituents was developed, which is characterized by an asymmetric Michael addition reaction of a chiral lithium amide with trisubstituted ( E )-α, β-unsaturated esters. We found that a highly face-selective protonation occurred by the quick addition of water to the enolate intermediate derived from the Michael addition reaction to afford N -protected β 2, 3 -amino esters in moderate to excellent yields. This finding was made possible by the facile preparation of geometrically pure trisubstituted ( E )-α, β-unsaturated esters, which was established recently by our group. The subsequent deprotection of the amino group in the Michael adduct by using N -iodosuccinimide (NIS) efficiently provided β 2, 3 -amino esters having various substituents. Graphical abstract: